THE ROLE OF GRIT AS A MODERATOR IN THE RELATIONSHIP BETWEEN JOB INSECURITY AND ORGANIZATIONAL COMMITMENT - Salendu, Alice; Tania, Medisa Faradina; Anuar, Faizul Nizar (Universitas Mercu Buana Yogyakarta, 2021)
Job insecurity has become a phenomenon that often occurs in pandemic situations. The purpose of this study is to examine the relationship between job insecurity and organizational commitment as a variable and at the level of dimension. In addition, this study explores the moderating role of grit on the relationship between job insecurityÂ Â and organizational commitment, especially during the pandemic which has an impact on many cases of layoffs. Participants were 200 employees who were obtained online using the method of convenience sampling. This research is quantitative, using measuring tools, namely the Organizational Commitment Questionnaire, Job Insecurity Measurement, and The Grit Scale. The data processing method used is the hierarchical multiple regression test. The results showed that there was no significant relationship between job insecurity and overall organizational commitment, also at the level of dimension such as affective organizational commitment, continuance organizational commitment, and normative organizational commitment. In addition, there was no significant moderating role of grit in the relationship between organizational commitment and job insecurity. This indicates that someone who has high job insecurity does not necessarily have an impact on reduced commitment to the organization.